الحصاد المائي السطحي لحوض وادي السهل الغربي بهضبة البطنان باستخدام نظم المعلومات الجغرافية - صالح، محمود علي المبروك Saleh, Mahmoud Ali Al-Mabrouk; السبيعي، سليمان يحيى سليمان; المهدي، علي محمد (جامعة بنغازي - كلية التربية بالمرج, 2019)
The study of drainage basins and networks of any area is important in geological and geomorphological studies. The results can be used to identify the hydrological characteristics of the basins and also to infer the water budget and the quantity of water that can be. The study aims at building a database of the morphometric and hydrological characteristics of the basin of the western valley of the plain, which is one of the most important basins that extend in the northeastern part of the plateau. In order to achieve the objectives of the basin study, the descriptive approach, the analytical method and the quantitative statistical method were used. And satellite images of the region, in addition to field observations, and also relied on the technology of remote sensing and information systems geography in order to identify and estimate the amount of surface salts and harvesting of surface saline water for the basin of the Valley of the Sahel, Hydrology and Water Budget of the Basin The morphometric parameters of Wadi Al-Sahl al-Gharbi were extracted. The digital height model (DEM) was calculated with a precision of 12 meters from the satellite vision by determining the basin boundary, to build basin net work by using Arc GIS programming.
إن دراسة أحواض وشبكات التصريف لأي منطقة ذات أهمية في الدراسات الجيولوجية والجيومورفولوجية، إذ يمكن استخدام نتائجها في التعرف على الخصائص الهيدرولوجية للأحواض كما يمكن من خلالها استنتاج الميزانية المائية وكمية المياه التي يمكن. تهدف الدراسة إلى بناء قاعدة معلومات للخصائص المورفومترية والهيدرولوجية لحوض وادي السهل الغربي الذي يعد من أهم الأحواض التي تمتد في الجزء الشمالي الشرقي من هضبة البطنان، ولتحقيق أهداف دراسة الحوض، تم استخدام المنهج الوصفي والمنهج التحليلي والمنهج الكمي الإحصائي، وقد اعتمدت الدراسة على الخرائط الجيولوجية والطبوغرافيا وصور الأقمار الصناعية للمنطقة، بالإضافة إلى المشاهدات الميدانية، كما اعتمدت أيضاً على تقنية الاستشعار عن بعد ونظم المعلومات الجغرافية بهدف تحديد وتقدير كمية السيح السطحي وحصاد مياه السيح السطحي لحوض وادي السهل، ولدراسة الخصائص الهيدرولوجية والميزانية المائية للحوض تم استخراج المعاملات المورفومتريةMorphometric properties لوادي السهل الغربي، حيث تم الاعتماد على نموذج الارتفاع الرقمي (DEM) digital elevation model بدقة 12 متر من المرئية الفضائية SRTM من خلال تحديد حدود الحوض، وبناء شبكات التصريف، وذلك باستخدام برنامج Arc Gis 10.2
Keywords: ليبيا -- الموارد المائية -- حصاد المياه -- المياه السطحية -- نظم المعلومات الجغرافية